Morphological Transformations during In Situ Electrochemical Generation of 2-Dimensional Co3O4 Hexagonal Nanoplates. Issue 2 (10th November 2015) - Liu, Siyang; Li, Longjun; Patterson, Nicholas A.; Manthiram, Arumugam
Abstract : In situ electrochemical generation of 2-dimensional Co3 O4 (2D-Co3 O4 ) nanoplates has been achieved by anodizing CoOx /Co precursors in 1 M KOH solution. X-ray diffraction characterization suggests that the CoOx /Co precursor is oxidized to Co3 O4 before the onset potential of oxygen evolution reaction (OER). Scanning electron microscopy shows that instead of retaining its original morphology, the irregular-shaped nanoparticles undergo a morphological transition into hexagonal nanoplates during the oxidation process. The mechanism of the morphological changes is discussed and a two-step topotactic transformation pathway from Co(OH)2 to CoOOH to Co3 O4 is proposed. Amorphization and recrystallization of the catalysts are also found at different stages of the electrochemical measurements. The 2D-Co3 O4 nanoplates exhibit high OER catalytic activity.